Peningkatan Literasi Informasi Televisi Bagi Aparatur Desa Sebagai Sarana Validasi Berita Bohong (Hoaks) di Desa Smartpolitan Wantilan Kabupaten Subang - Tresia Wulandari; Kiki Nurjaman; Lisma Nadia Laehmanah; Ziqra Adhi Hamzah (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
Smartpolitan Village is a village development concept that integrates information and communication technology (ICT) in resource management and public services to improve the quality of life of the community. For this reason, this Community Service activity is entitled "Improving Television Information Literacy for Village Officials as a Means of Validating Fake News (Hoaxes) in Smartpolitan Village Wantilan, Subang Regency". The aim is to implement the Tri Dharma of Higher Education and assist partners in improving their ability to develop an understanding of information literacy towards a Smartpolitan Village. Limited digital literacy of the community and the vulnerability of the community to the spread of hoaxes. Therefore, efforts are needed to improve the digital literacy of the community and utilize television as a medium for validating fake news so that Wantilan Village can truly become a Smartpolitan Village that is smart, informative, and resilient to hoaxes. Based on the identification of problems with partners, the team provides solutions and methods that can overcome these problems through: 1. Providing basic introductory material on fake news and how to validate information through television which is used as knowledge. 2. Providing direction in the form of material, techniques for preventing the spread of hoax news and the impacts of spreading or consuming fake news without validating it. 3. Conducting assistance in the practice of validating television media information. Based on the solutions and output targets achieved from the implementation of the PKM program on partners, village officials and residents in Wantilan Village, Cipeundeuy District, Subang Regency, the Community Service Team determined the approach method with: 1. Direction and training 2. Technical Guidance (Bimteks) 3. Mentoring